OTA Testing for Massive MIMO Devices Using Cascaded APM Networks and Channel Emulators - Lijian Xin; Yong Li; Hao Sun; Xiang Zhang (International Journal of Antennas and Propagation)
This paper proposes an over-the-air (OTA) testing setup for millimeter-wave (mmWave) massive multiple-input multiple-output (MIMO) equipment using cascaded amplitude and phase modulation (APM) network and channel emulator. Compared with the existing test setup with mechanical switch, the proposed testing setup enables more accurate reconstruction of the radio channel environment under the multiprobe anechoic chamber (MPAC) setup without increasing the number of channel emulators (CEs) to control the system cost. The constructed MPAC testing setup for mmWave and massive MIMO equipment is composed of an anechoic chamber, a sectored probe wall containing a number of probes, an APM network, a fading channel emulator, and a user emulator (UE). In this paper, the structural model and the performance advantages of the proposed radiated testing setup are described, and a fully connected APM network for radiated testing is more prominent than the existing switch. Moreover, the angular spectrum is selected as the performance metric for the reconstructed channel. The ability of the proposed system to reconstruct the power angular spectrum (PAS) of the target channel is studied under both static and dynamic channel models, which can reflect the performance of beamforming procedures of the massive MIMO antenna arrays, e.g., beam acquisition, tracking, and refinement. The simulation results for angular spectrum support the superiority of the proposed OTA testing setup. Furthermore, the simulations for average channel capacity also show that radiated testing setup using cascaded APM network and channel emulator is valid.